Evaluating crystal-orientation-dependent properties on polycrystalline tungsten: Example oxidation. (April 2020) - Schlueter, Karsten; Balden, Martin; da Silva, Tiago Fiorini
Abstract: Various material properties, like oxidation, depend on the surface orientation of crystals. Most evaluations are focused on a few crystal orientations or using single crystals. A software tool written in python is introduced to correlate the thickness of the tungsten (W) oxide layer, i.e., the oxidation rate, and the individual single crystal grains with their surface orientation of polycrystalline W. The results are visualized in an inverse pole figure, which represent the oxidation rates for all crystal orientations. The use of polycrystalline W samples allows to analyze many different crystal orientations in a single experiment. Recrystallized, polished and polycrystalline W samples were pre-characterized using electron backscatter diffraction in a scanning electron microscope (SEM). Subsequently, the samples were oxidized in a thermobalance. A confocal laser scanning microscope was used for measuring the height of the oxide layer, which is scaled to thickness of the oxide layer by using SEM images from focused ion beam prepared cross-sections. Previous data of oxidation of W in the temperature range of 720 K to 870 K were reanalyzed with the new analysis tool. At grain boundaries, the oxidation is influenced by the neighboring grains. To evaluate the magnitude of this effect on the oxidation, samples with different textures were oxidized and evaluated. The results for the different textures agree within the estimated error bars, demonstrating the effectiveness of the automated analysis method. W grains with 〈100〉 surface orientation showed the highest oxidation rate. Highlights: Method to measure and evaluate orientation of many single crystal grains with a python tool Visualize the oxidation rate in an inverse pole figure The oxidation rate vary by a factor of two in temperature range 720 to 870 K. Orientation-dependent oxidation is different for a nm thick oxide layer and a μm thick oxide layer.